2016
DOI: 10.18632/oncotarget.9552
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of protein kinase C and p53-MDM2 or PKC and mTORC1 are novel efficient therapeutic approaches for uveal melanoma

Abstract: Uveal melanoma (UM) is the most common cancer of the eye in adults. Many UM patients develop metastases for which no curative treatment has been identified. Novel therapeutic approaches are therefore urgently needed. UM is characterized by mutations in the genes GNAQ and GNA11 which activate the PKC pathway, leading to the use of PKC inhibitors as a rational strategy to treat UM tumors. Encouraging clinical activity has been noted in UM patients treated with PKC inhibitors. However, it is likely that curative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…Furthermore, the inhibitors caused a strong synergistic growth inhibitory effect on UM cell lines and marked tumor regression in UM xenograft models. Recently, screening of drug combinations involving AEB701 in a large panel of UM patient-derived xenografts (PDX) also determined two non MEK inhibitors that could potentially be used in combination with PKC inhibitors as therapeutic strategies for metastatic UM (47). These were the p53-MDM2 inhibitor, CGM097 and the mTORC1 inhibitor, RAD001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the inhibitors caused a strong synergistic growth inhibitory effect on UM cell lines and marked tumor regression in UM xenograft models. Recently, screening of drug combinations involving AEB701 in a large panel of UM patient-derived xenografts (PDX) also determined two non MEK inhibitors that could potentially be used in combination with PKC inhibitors as therapeutic strategies for metastatic UM (47). These were the p53-MDM2 inhibitor, CGM097 and the mTORC1 inhibitor, RAD001.…”
Section: Introductionmentioning
confidence: 99%
“…These were the p53-MDM2 inhibitor, CGM097 and the mTORC1 inhibitor, RAD001. AEB701 and CGM097 or AEB701 and RAD001 markedly reduced tumor growth and induced tumor regression (47). These studies provide evidence for a number of targeted therapies that may be evaluated in combination with MEK inhibitors or PKC inhibitors in clinical studies to improve the survival of patients with metastatic UM.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al, 2014). Novartis laboratories have also developed a novel MDM2:p53 protein inhibitor, a dihydroisoquinolinone derivative called NVP-CGM097, which, in addition to in vitro efficacy studies for AML and uveal melanoma, is currently undergoing phase I clinical trials in patients with selected advanced solid tumors (Carita et al, 2016; Holzer et al, 2015; Weisberg et al, 2015) (NCT01760525). Analysis of patient tumors by intersecting high-throughput cell line sensitivity data with genomic data from the ongoing trial has identified distinct p53 target genes that predict sensitivity to NVP-CGM097, a genetic signature that can be used for selection of patients that would be most sensitive to treatment with NVP-CGM097 or other MDM2 antagonists (Jeay et al, 2015).…”
Section: Small Molecule Wild-type P53 Activatorsmentioning
confidence: 99%
“…Combined treatment of MAPK and PKC inhibitors demonstrated synergistic antitumor effects [70]. Dual inhibitions of PKC/p53-MDM2 and PKC/mTORC1 were also found to regress preclinical models of metastatic UM tumors in a synergistic manner [71]. …”
Section: Uveal Melanomamentioning
confidence: 99%